3d printed cortical tissue and implantation - Jin, Y (2023)
It is a considerable challenge to engineer human tissue with multiple cell types and a defined cellular structure and function. The outer layer of the brain, the cerebral cortex, is composed of a layered architecture, which consists of multiple types of layer-specific neurons arranged into vertical columns. The layered structures enable higher cognition via intricately wired neuronal circuits; however, the present tissue engineering technique cannot generate these structures. In the current DPhil project, we used a droplet-based bioprinting technique to assemble living tissues mimicking simplified cerebral cortical columns. Upper- and deep-layer cortical neural progenitors were differentiated from human-induced pluripotent stem cells (hiPSCs) and were then droplet printed into two-layered cerebral cortical tissues. In the subsequent characterization, we found that the tissues demonstrated layer-specific biomarker expression and produced an integrated axon network. The printed cerebral cortical tissues were implanted into mouse brain explants, which revealed a considerable host–implant connection across the boundaries via axon projection, neuron migration, and the establishment of correlated calcium ion signals. Implanted brain explants can be applied in the evaluation of compounds and nutrients that facilitate tissue integration. Moreover, our technique might be used in personalized implantation therapy by 3D-printed tissues generated from patients’ own iPSCs.